A novel synthetised sulphonylhydrazone coumarin (E)‐4‐methyl‐N′‐(1‐(3‐oxo‐3H‐benzo[f]chromen‐2‐ yl)ethylidene)benzenesulphonohydrazide protect against isoproterenol‐induced myocardial infarction in rats by attenuating oxidative damage, biological changes and electrocardiogram - Ghazouani, Lakhdar; Khdhiri, Emna; Elmufti, Afoua; Zarei, Armin; Feriani, Anouar; Baaziz, Intissar; Hajji, Raouf; Abid, Majdi; Ammar, Houcine; Abid, Souhir; Allouche, Noureddine; Mnafgui, Kais; et al. (Clinical and experimental pharmacology & physiology, 2022)
Coumarins and their derivatives are becoming a potential source for new drug discovery due to their vast array of biological activities. The present study was designed to investigate the cardioprotective effects of a newly synthesised coumarin, symbolised as 5,6‐PhSHC, against cardiac remodelling process in isoproterenol (ISO) induced myocardial infarction (MI) in male Wistar rats by evaluating haematological, biochemical and cardiac biomarkers. Rats were pre/co‐treated with 5,6‐PhSHC or clopidogrel (150 μg/kg body weight) daily for a period of 7 days and then MI was induced by injecting ISO (85 mg/kg body weight), at an interval of 24 hours for 2 consecutive days, on the sixth and seventh days. The in vivo exploration indicated that the injection of 5,6‐PhSHC improved the electrocardiographic (ECG) pattern and prevented severe heart damage by reducing leakage of the cardiac injury markers, such as troponin‐T (cTn‐T), lactate dehydrogenase (LDH), and creatine kinase‐MB. The cellular architecture of cardiac sections, altered in the myocardium of infracted rats, was reversed by 5,6‐PhSHC treatment. Results showed that injection of 5,6‐PhSHC elicited significant cardioprotective effects by prevention of myocardium cell necrosis and inflammatory cells infiltration, along with marked decrease in plasma levels of fibrinogen. In addition, the total cholesterol, triglyceride, LDL‐c, and HDL profiles underwent remarkable beneficial changes. It was also interesting to note that 5,6‐PhSHC enhanced the antioxidative defence mechanisms by increasing myocardial glutathione (GSH) level, superoxide dismutase (SOD), and catalase (CAT) activities, together with reducing the levels of thiobarbituric‐acid‐reactive substances (TBARS), when compared with ISO‐induced rats. Taken together, these findings suggested a beneficial role for 5,6‐PhSHC against ISO‐induced MI in rats. Furthermore, in silico analysis showed that 5,6‐PhSHC possess high computational affinities (E‐value >−9.0 kcal/mol) against cyclooxygenase‐2 (PDB‐ID: 1CX2), vitamin K epoxide reductase (PDB‐ID: 3KP9), glycoprotein‐IIb/IIIa (PDB‐ID: 2VDM) and catalase (PDB‐ID: 1DGF). Therefore, the present study provided promising data that the newly synthesised coumarin can be useful in the design and synthesis of novel drug against myocardial infarction.